Family-centered Care for Sick Newborns: A Thumbnail View - Maria, Arti (Indian J Community Med, 2016)
Family-centered care (FCC) for sick newborns is emerging as a paradigmatic shift in the practice of facility-based newborn care. It seeks to transforming a provider-centered model into a client-centered one and thus build a new therapeutic alliance. FCC is the cornerstone of continuum of care, imparting caregiving competencies to parents/caregivers both within institutions as well as after the discharge. This has potential gains for the newborn, family members, and facility-level staff. The initial model piloted in tertiary-care settings is now undergoing translation at five sites across the country; the outcomes are keenly awaited.